FORMATION OF INTERNAL ECONOMIC REPORT ON FURTHER EXPENDITURE ON FIXED ASSETS OF OIL AND GAS COMPLEX ENTERPRISES - Kafka, S.M. (The actual problems of regional economy development, 2019)
The article is aimed at exploring the current approaches to accounting for further costs of fixed assets, as they are not straightforward and are constantly changing due to processes occurring in the legal and economic environment, but have a significant impact on the formation of accounting information about the entity's fixed assets, its expenses, and ultimately the profit of the enterprise during the reporting period. For oil and gas enterprises, the issue of accounting for transactions related to the repair and modernization of fixed assets is relevant given the need to improve their work due to significant wear and tear and loss of initial technical characteristics in a competitive environment. In the current accounting procedure, even eliminating minor damage by replacing costly parts can affect the financial result of the period in which it was carried out, which distorts information about the results of the enterprise activity. Processes for collecting, registering and accumulating operational information on further expenditures on fixed assets in a single management register have been improved, enabling the necessary amount of information to be analyzed and making effective decisions about the feasibility of further exploitation of certain fixed assets, or their replacement or modernization, organization of repair works in the economic way, or with the involvement of specialized third-party organizations, etc. The results of the study are aimed at increasing the reliability, efficiency and analytical accounting for the costs of operation, maintenance and restoration of fixed assets and enable the identification and use of internal reserves to improve the activities of enterprises.